2004
DOI: 10.1111/j.1365-2958.2004.04003.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative control of Listeria monocytogenes virulence genes by a diffusible autorepressor

Abstract: SummaryVirulence genes from the facultative intracellular pathogen Listeria mono cytogenes are controlled by the transcriptional regulator PrfA. Although PrfA synthesis is activated at 37 ∞ ∞ ∞ ∞ C, PrfA-dependent expression remains low in rich medium. However, a strong induction of the PrfA regulon is observed when L. monocytogenes is cultured in the presence of activated charcoal. Here, we show that the 'charcoal effect' results from the adsorption of a diffusible autorepressor substance released by L. monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 41 publications
5
65
1
2
Order By: Relevance
“…Group I contains all known PrfA-dependent virulence genes, including the genes encoding LIPI-I (57), inlAB, inlC, and hpt. Up-regulation of these genes clearly correlates with the activity of PrfA, since greater up-regulation was observed with the hyperactive molecule PrfA* than with equal amounts of wild-type PrfA, which is in accord with other reports (13). It is interesting that expression of none of the genes which were recently reported to be also under PrfA control, like bsh, bilE, or vip (5,11,50), was found to be up-regulated under these conditions, suggesting that these genes are controlled differently by PrfA than the "classic" PrfA-regulated virulence genes mentioned above.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Group I contains all known PrfA-dependent virulence genes, including the genes encoding LIPI-I (57), inlAB, inlC, and hpt. Up-regulation of these genes clearly correlates with the activity of PrfA, since greater up-regulation was observed with the hyperactive molecule PrfA* than with equal amounts of wild-type PrfA, which is in accord with other reports (13). It is interesting that expression of none of the genes which were recently reported to be also under PrfA control, like bsh, bilE, or vip (5,11,50), was found to be up-regulated under these conditions, suggesting that these genes are controlled differently by PrfA than the "classic" PrfA-regulated virulence genes mentioned above.…”
Section: Discussionsupporting
confidence: 81%
“…Our data led us to conclude that high concentrations of wild-type PrfA and of PrfA* inhibit PTS-mediated glucose transport probably by binding to a component essential for this process. Several previous studies (2,4,13,34,37) have shown that PrfA activity is inhibited by an unknown mechanism when L. monocytogenes is cultured in the presence of PTS sugars, like glucose and especially cellobiose. Both observations may be based on the interaction of PrfA with a common component involved in the PTS-mediated uptake of these sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Although we are aware that such in vitro transcription systems may not necessarily reflect the in vivo situation, these in vitro data suggest that PrfA activity may be modulated in vivo by negatively acting factor(s), at least in addition to positively acting co-factor(s). A similar conclusion has also been reached in studies performed by Ermolaeva et al (2004).…”
Section: Introductionsupporting
confidence: 75%
“…Furthermore, there is evidence for the interaction of PrfA with other listerial factors that modulate its activity (6,7,16,19). Mutations within specific regions of PrfA have been obtained (45,52,56,64,65,68) which lead to a permanently active state of PrfA; e.g., the addition of activated charcoal to brain heart infusion (BHI) medium or incubation in minimal essential medium (MEM) does not cause further activation, and cellobiose no longer inhibits the activity of these mutant PrfA proteins (termed PrfA*).…”
mentioning
confidence: 99%